Teachers’ Strategies in Promoting Religious Moderation in Islamic Primary Education: A Case Study at MI Nurul Huda Bondowoso - Ahmad Izzuddin Faqih; Abd Muhith; Mashudi (ATTA`DIB, 2026)
This study aims to examine teachers’ strategies in promoting religious moderation in Islamic primary education at MI Nurul Huda Bondowoso. Religious moderation is a crucial issue in Islamic education to cultivate balanced, tolerant, and non-extreme attitudes from an early age. This research employed a qualitative case study design involving Islamic Religious Education teachers and classroom teachers selected purposively. Data were collected through in-depth interviews and classroom observations and analyzed using thematic analysis, including data reduction, data display, and conclusion drawing. The findings show that teachers generally understand religious moderation as a balanced (wasatiyyah), tolerant, and respectful attitude. Strategies used include integrating moderation values into lesson content, applying storytelling based on prophetic role models, demonstrating moderate behavior, and fostering respectful classroom communication. These practices contribute to a positive classroom climate characterized by mutual respect and constructive conflict management. However, the implementation of dialogical and student-centered learning remains inconsistent. This study implies the need to strengthen teachers’ conceptual understanding and pedagogical competence, particularly in dialogical learning approaches. Additionally, institutional support through systematic training and clear pedagogical guidelines is essential to ensure consistent and effective implementation of religious moderation in Islamic primary education.